2017
DOI: 10.4102/hts.v73i3.4548
|View full text |Cite
|
Sign up to set email alerts
|

Commercialisation of theological education as a challenge in the Neo-Pentecostal Charismatic churches

Abstract: Commercialisation, technology, and globalisation impact all facets of religion.Commercialisation of religion contributes towards society’s obsession with success. One areathrough which commercialisation manifests itself is in theological education. This isexacerbated by the celebrity cult whereby the leader’s success is measured by wealthyappearance. The current legal accreditation requirements put pressure on the Neo-PentecostalCharismatic ministerial formation. The online courses come at a high price, as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, those with little or no knowledge in theological education (1-3 persons representing 12.5-37.5%) may not have attended formal Bible schools where proper theology is taught. They may resort to reliance on the Holy Spirit and unreliable sources as predicted by Resane (2017). He argued that lack of proper theological education makes church leaders to be gullible to inadequate doctrinal focus.…”
Section: Extent To Which Church Ministers/pastors/leaders Were Knowledgeable In Theological Educationmentioning
confidence: 99%
“…However, those with little or no knowledge in theological education (1-3 persons representing 12.5-37.5%) may not have attended formal Bible schools where proper theology is taught. They may resort to reliance on the Holy Spirit and unreliable sources as predicted by Resane (2017). He argued that lack of proper theological education makes church leaders to be gullible to inadequate doctrinal focus.…”
Section: Extent To Which Church Ministers/pastors/leaders Were Knowledgeable In Theological Educationmentioning
confidence: 99%
“…Regrettably, the gains of the internet and social media have been lost in the disillusionment caused by the brazen abuse by both the clergy and impostors who have deployed the privacy of the platform for commercialization of religious worship (Resane, 2017;Gilbert, 2015;Chiluwa, 2012;2013). Chiluwa's (2012) study on online religion in Nigeria: the internet church and cyber miracles revealed that the positive characteristics of the Internet platform have been exploited to mislead unsuspecting worshippers for commercial gains.…”
Section: Religious Multiplicity: An Inquiry Into the Psychological Usmentioning
confidence: 99%
“…In the context of the current discussion on the commercialisation of religion, this means that services provided to members by a church body have a price tag, overtly or covertly. In explaining this concept, Gitonga (2011, cited in Resane 2018) says that commercialisation of the Gospel is the presentation of the Biblical message either as a commodity for sale for material gain or as an object of investment for personal aggrandisement. The author further refers to the sale of spiritual benefits, such as spiritual healing and offer of prayers for special needs.…”
Section: The Concept Commercialisationmentioning
confidence: 99%
“…In some instances, church members have to buy church products in order to receive God's blessings. In his article on the commercialisation of theological education, Resane (2017) shows that the main characteristic of a commercialised group is that of a "celebrity cult" where members elevate the leader to some high status of beauty, achievement, prestige and power. Shupe, Stacey and Darnell (2000, cited in Resane 2017) also confirm that possessions like vehicles, clothing and buildings represent the success that congregants yearn to possess and they put the leader on a pedestal of "a divine being whose will is that of God and whose actions are above reproach".…”
Section: The Concept Commodificationmentioning
confidence: 99%
See 1 more Smart Citation